Conservat ion of Indigenous Wild Edible Plants Used by Different Communit ies of Kangchup Hills, Senapat i, North East India - Khan, M. R.; Kikim, A.; Yadava, P. S. (International Journal of Bio-resource and Stress Management, 2023)
Several wild plants have been used as food by tribals and other local people living in and around the forest areas in North East India. The diversity of wild species not only offers varieties in family food diet and contribute to household food security but offer also in generation of income by selling the excessive food plants in the local markets. The study area is located in between 24°45΄-24°51΄ N latitude and 93°48΄-93°55΄E longitudes at Kangchup hills, Senapati District of Manipur state at an altitude ranging from 865 m to 1785 m above mean sea level. The study was undertaken to survey and documentation of wild edible plants for three years from January 2011 to December 2013. 52 species of wild edibles belonging to 47 genera and 38 families were recorded out of which 26 were vegetables, 15 fruits and 11 spices/aromatic plant species from the study area. The study area is inhabited by different ethnic groups i.e. Thadou (Kuki), Vaiphei, Chiru, Ireng (Rongmei) and Meitei. Some edible plants have great economic value and are highly linked with socio-economic development of tribal communities of the state. Most of them in these areas depends on forest products for their livelihood. The traditional knowledge on wild food plants is declining day by day due to overexploitation and biotic disturbances in the forest ecosystems. Therefore the present study emphasized the need for the protection and conservation of these wild edible plant species for the benefit of human mankind and future generations.